Seizure-Precipitating Factors in Relation to medical Recommendations: Especially Those Limiting Physical Activity. (October 2015) - Stanuszek, Agnieszka; Wnękowicz, Emilia; Kuźniar, Ewelina; Krakowska, Karolina; Gergont, Aleksandra; Kaciński, Marek
Identification of factors precipitating epileptic seizures should always have practical implications and should always result in special recommendations given to patients. The purpose of our study is to analyze the relation between seizure-triggering factors and restrictive recommendations involving limitation of physical activity in particular. The research group consisted of 407 children hospitalized due to seizures. Their precipitants were identified in 27.5% of the patients. The most common included infection/fever, stress, and flashing lights. Although sport was documented as a precipitant in only 3.4% of all children, 8.1% of the investigated group were recommended to limit physical activity. As some episodes of epileptic seizures are reported to be provoked by sport, multiple restrictions are imposed on children. In the light of the worldwide academic literature and the present study, the recommendation of limiting sports activity is no longer supported.